STRATEGIC MANAGERIAL ANALYSIS OF PT MULTI MEDIKA RAHARJO: A COMPETITIVE ADVANTAGE APPROACH - Julian Petra Hernando Kaaro; Indarto Indarto; Adjiati Utaminingsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
The vast development of medical device industry has led to the establishment of medical device distributor as a key agent in ensuring product availability, quality, and regulatory compliance. PT Multi Medika Raharjo is a medical device distributor company established in 2005, whose distribution focus primarily in Central Java and DIY. The COVID-19 pandemic along with the regulations of the Ministry of Industry and Ministry of Health encouraging the use of domestic production equipment, marked a leap on the medical device distributor company development, and the higher level of competition between companies. This study aims to analyze the competitive advantage strategy of PT Multi Medika Raharjo. Employing qualitative approach, this study examined the competitive advantage strategy of PT Multi Medika Raharjo, based on the data collected in the field. The primary data were obtained from in-depth interview techniques and observations involving the company CEO, technical manager, and marketing staff. The secondary data were obtained through literature review. In analyzing the data, the researcher implemented Porter and Houma's competitive advantage theory. The study concluded that there are several competitive advantage strategies implemented by PT Multi Medika Raharjo. The company established HR development to improve the quality of synergistic product output, acquired CDAKB and ISO 9001:2015 certification and ensures that the sub-distributors acquired the same certification to maintain the quality of a product. Furthermore, PT Multi Medica Raharjo aims to conduct their business mainly in Central Java and DIY area to be able to identify their target segments by conducting in-depth market analysis.